Pemanfaatan Sisa Ampas Tebu Menjadi Aksesori Interior - Shania Regina Ferdinandus; Mochamad Junaidi Hidayat (Meraki: Journal of Creative Industries, 2024)
The large amount of bagasse that is not utilized and left to accumulate over a period of time will risk environmental pollution. Therefore, with the main objective of reducing the amount of bagasse that accumulates, researchers will utilize the remaining bagasse into products that have selling value as well as can create new business opportunities. For this reason, an experimental method will be used, with this method researchers can find out more about bagasse so that it can be used as a product. The experimental stages carried out begin with sorting, softening, separating, drying, coloring, pattern formation, and ending with finishing. In this experiment, it was found that the most effective shaping process using the bagasse powder pressing technique with wood glue produced a sturdy and rough-textured character. By considering the experimental results, the type of product to be made is an interior accessory consisting of three products, namely a mirror, wall clock, and tissue holder.